2003
DOI: 10.1139/b03-141
|View full text |Cite
|
Sign up to set email alerts
|

From genotype to phenotype: unraveling the complexities of cold adaptation in forest trees

Abstract: Adaptation to winter cold in temperate and boreal trees involves complex genetic, physiological, and developmental processes. Genecological studies demonstrate the existence of steep genetic clines for cold adaptation traits in relation to environmental (mostly temperature related) gradients. Population differentiation is generally stronger for cold adaptation traits than for other quantitative traits and allozymes. Therefore, these traits appear to be under strong natural selection. Nonetheless, high levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
556
5
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 453 publications
(612 citation statements)
references
References 129 publications
(166 reference statements)
37
556
5
5
Order By: Relevance
“…Furthermore, most previous studies have demonstrated that juvenile age classes are likely to be more sensitive to environmental stress (e.g., temperature and moisture) than mature trees (Howe et al, 2004;Greenwood et al, 2008), with less research focusing on the ecophysiological performances of younger, and smaller life stages. In this case, experimental warming stimulated the growth in both age classes.…”
Section: Differences In Growth and Photosynthesis Between Age Classesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, most previous studies have demonstrated that juvenile age classes are likely to be more sensitive to environmental stress (e.g., temperature and moisture) than mature trees (Howe et al, 2004;Greenwood et al, 2008), with less research focusing on the ecophysiological performances of younger, and smaller life stages. In this case, experimental warming stimulated the growth in both age classes.…”
Section: Differences In Growth and Photosynthesis Between Age Classesmentioning
confidence: 99%
“…Furthermore, many previous studies have demonstrated that juvenile age trees may be more sensitive to environmental changes (i.e., temperature, moisture) than mature trees (Howe et al, 2004;Greenwood et al, 2008), with less research focusing on the ecophysiological performances of younger, and smaller life stages (Reinhardt et al, 2009). Comparative studies of different growth stages may provide essential information for understanding the strategies adopted by the species at different stages of their life cycle, as well as the selective pressures that operate in each stage (Mediavilla and Escudero, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…By treating populations within a widespread species as an undifferentiated collection of individuals, differences in many physiological, ecological, and growth attributes are discounted and the assessment of climate change effects may result in a false net positive impact on forest productivity (herein considered only as area-base suitable habitat) [17][18][19]. However, among-population variation resulting from climate-related natural selection and local adaptation is widely observed along climatic gradients [20,21]. Ecological genetics studies such as provenance testing have revealed that the adaptability of different geographic populations can differ substantially [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Across their broad ranges, such species span large environmental gradients, and populations are often locally adapted. For example, growth and phenology traits are moderately to strongly heritable and display climatic clines (Howe et al, 2003;Savolainen et al, 2007). Furthermore, repeated Quaternary glacial cycles have had a pronounced effect, seen in both the past and current distribution of species, even in areas that were free of ice during the last glacial maximum (LGM, ca 18 000 years ago; Frenzel et al, 1992;Jackson and Weng, 1999;Hu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Investigating patterns of diversity across putatively neutral and potentially adaptive genes controlling ecologically important traits can provide insight into the importance of neutral demographic and selective forces in forest trees (Ma et al, 2010), identify potential targets for tree breeding programs (Howe et al, 2003) and aid conservation practices by clarifying the role of climate change as a driver of evolution (Savolainen et al, 2007;Alberto et al, 2013). In areas covered by ice sheets during the LGM, several studies have found evidence of recent expansion.…”
Section: Introductionmentioning
confidence: 99%